Kleptoparasitism during courtship in Sterna hirundo and its relationship with female reproductive performance - García, Germán Oscar; Becker, Peter H.; Favero, Marco (Journal of Ornithology)
Kleptoparasitism is a well-known foraging tactic used opportunistically by many seabird species. However, little is known about this behaviour during the early stages of the breeding cycle and its effects on breeding performance. Here, we investigated the relationship between kleptoparasitism during the courtship period and female reproductive performance in Common Terns (Sterna hirundo). All identified kleptoparasites were males, and none of their mates performed such behaviour. We compared two groups of tern pairs, one where the males performed kleptoparasitism (kleptoparasitic group, n = 10), the other one where both mates were non-kleptoparasitic (honest group, n = 22). The body mass of kleptoparasitic females was between 8 and 15% higher than that of honest females. In kleptoparasitic females, the third egg was significantly bigger than in honest birds, and the egg-volume was not significantly different between the three eggs of the clutch in contrast to honest birds. We found no differences in the comparison among hatching success between both groups. The reproductive output, however, was significantly higher in the kleptoparasitic than in the honest group. Hence, we are providing the first evidence that kleptoparasitism during early stages of the breeding cycle has a strong link with egg size and reproductive output in Common Terns. Fil: García, Germán Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Becker, Peter H. Institut Fur Vogelforschung "vogelwarte Helgoland"; Alemania Fil: Favero, Marco. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. ...